(untitled) (LEGAL DIALOGICA, 2025)
This research focuses on efforts to identify, examine, and evaluate policies implemented by village governments in implementing infrastructure development, with reference to the legal provisions and regulations in force in Indonesia. The approach used in this research is a normative approach, a type of legal research that relies on the analysis of secondary legal materials. This method falls under the category of library research, with a primary focus on examining the legal norms that form the basis of the study. The materials used include relevant laws and regulations, legal books, scientific articles, journals, research reports, papers, and other relevant sources related to the issue under study. The findings of this study indicate that villages are sovereign entities, a recognition that has grown stronger since the enactment of the Village Law. For a long time, the government has implemented various policies and programs to encourage development in rural areas, with the primary goal of improving community welfare through the optimal use of available resources. One development strategy stipulated in Law Number 6 of 2014 concerning Villages is an integrated rural development approach, known as the rural area development program. The diversity of regional characteristics, development approaches, and other elements within this program have enriched the experience and practice of village development. The recommendation in this study is that the village government needs to ensure that all elements of society are actively involved in the supervision, preparation, and implementation of village development so that the programs implemented are commensurate with the needs and aspirations of the local community. Abstrak: Penelitian ini difokuskan pada upaya untuk mengidentifikasi, menelaah, serta mengevaluasi kebijakan yang diterapkan oleh pemerintah desa dalam pelaksanaan pembangunan infrastruktur, dengan merujuk pada ketentuan hukum dan peraturan perundang-undangan yang berlaku di Indonesia. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan normatif, yaitu jenis penelitian hukum yang bertumpu pada analisis bahan hukum sekunder. Metode ini termasuk dalam penelitian kepustakaan, dengan fokus utama pada penelaahan norma-norma hukum yang menjadi dasar kajian. Bahan yang digunakan mencakup peraturan perundang-undangan terkait, buku-buku hukum, artikel ilmiah, jurnal, laporan penelitian, makalah, serta sumber-sumber relevan lainnya yang berkaitan dengan isu yang diteliti. Temuan dalam penelitian ini menunjukkan bahwa desa merupakan entitas yang memiliki kedaulatan, yang pengakuannya semakin kuat sejak diberlakukannya Undang-Undang Desa. Sejak lama, pemerintah telah menerapkan berbagai kebijakan dan program untuk mendorong pembangunan di wilayah perdesaan dengan tujuan utama meningkatkan kesejahteraan masyarakat melalui optimalisasi pemanfaatan sumber daya yang tersedia. Salah satu strategi pembangunan yang diatur dalam Undang-Undang Nomor 6 Tahun 2014 tentang Desa adalah pendekatan pembangunan perdesaan secara terintegrasi, yang dikenal sebagai program pengembangan kawasan perdesaan. Keberagaman karakteristik wilayah, pendekatan pembangunan, serta elemen-elemen lainnya dalam program ini turut memperkaya pengalaman dan praktik dalam pembangunan di desa. Rekomendasi dalam penelitian ini adalah diharapkan pemerintah desa perlu memastikan seluruh elemen masyarakat terlibat aktif dalam pengawasan, persiapan, dan pelaksanaan pembangunan desa agar program yang dijalankan sebanding kebutuhan dan aspirasi masyarakat lokal.